Porous Microspheres Comprising CoSe2 Nanorods Coated with N-Doped Graphitic C and Polydopamine-Derived C as Anodes for Long-Lived Na-Ion Batteries - Jae Seob Lee; Rakesh Saroha; Jung Sang Cho (Nano-Micro Letters, 2022)
Abstract Metal–organic framework-templated nitrogen-doped graphitic carbon (NGC) and polydopamine-derived carbon (PDA-derived C)-double coated one-dimensional CoSe2 nanorods supported highly porous three-dimensional microspheres are introduced as anodes for excellent Na-ion batteries, particularly with long-lived cycle under carbonate-based electrolyte system. The microspheres uniformly composed of ZIF-67 polyhedrons and polystyrene nanobeads (ϕ = 40 nm) are synthesized using the facile spray pyrolysis technique, followed by the selenization process (P-CoSe2@NGC NR). Further, the PDA-derived C-coated microspheres are obtained using a solution-based coating approach and the subsequent carbonization process (P-CoSe2@PDA-C NR). The rational synthesis approach benefited from the synergistic effects of dual carbon coating, resulting in a highly conductive and porous nanostructure that could facilitate rapid diffusion of charge species along with efficient electrolyte infiltration and effectively channelize the volume stress. Consequently, the prepared nanostructure exhibits extraordinary electrochemical performance, particularly the ultra-long cycle life stability. For instance, the advanced anode has a discharge capacity of 291 (1000th cycle, average capacity decay of 0.017%) and 142 mAh g−1 (5000th cycle, average capacity decay of 0.011%) at a current density of 0.5 and 2.0 A g−1, respectively.